The influence of combinations of oximes on the reactivating and therapeutic efficacy of antidotal treatment of tabun poisoning in rats and mice - Kassa, Jiri; Karasova, Jana Zdarova; Pavlikova, Ruzena; Misik, Jan; Caisberger, Filip; Bajgar, Jiri (Journal of applied toxicology, 2010)
The influence of the combination of oximes on the reactivating and therapeutic efficacy of antidotal treament of acute tabun poisoning was evaluated. The ability of two combinations of oximes (HI-6 + obidoxime and HI-6 + K203) to reactivate tabun-inhibited acetylcholinesterase and reduce acute toxicity of tabun was compared with the reactivating and therapeutic efficacy of antidotal treatment involving single oxime (HI-6, obidoxime, K203) using in vivo methods. Studies determining percentage of reactivation of tabun-inhibited blood and tissue acetylcholinesterase in poisoned rats showed that the reactivating efficacy of both combinations of oximes is higher than the reactivating efficacy of the most effective individual oxime in blood and diaphragm and comparable with the reactivating effects of the most effective individual oxime in brain. Moreover, both combinations of oximes were found to be slightly more efficacious in the reduction of acute lethal toxic effects in tabun-poisoned mice than the antidotal treatment involving individual oxime. A comparison of reactivating and therapeutic efficacy of individual oximes showed that the newly developed oxime K203 is slightly more effective than commonly used obidoxime and both of them are markedly more effective than the oxime HI-6. Based on the obtained data, we can conclude that the antidotal treatment involving chosen combinations of oximes brings beneficial effects for the potency of antidotal treatment to reactivate tabun-inhibited acetylcholinesterase in rats and to reduce acute toxicity of tabun in mice.
Keywords: Male; Rats, Wistar; acetylcholinesterasa; Acetylcholinesterase; antidota; Animals; potkani Wistar; obidoxim chlorid; Cholinesterase Reactivators; organofosfáty; pyridinové sloučeniny; Mice; reaktivátory cholinesterasy; mužské pohlaví; krysa rodu Rattus; oximy; Organophosphate Poisoning; otrava organofosfáty; Rats; kombinovaná farmakoterapie; Obidoxime Chloride; Pyridinium Compounds; zvířata; Organophosphates; Drug Therapy, Combination; Oximes; Antidotes; myši